Low power-delay-product (PDP) CMOS multiplier design - Leng, Xiaoxiang (Nanyang Technological University, 2021)
Multiplier is an important part of the microprocessor, which determines the performance of the system, and plays a pivotal role in image processing, speech recognition and other fields.